Control of tracheal tubulogenesis by Wingless signaling. - Chihara, T.; Hayashi, S. (Development, 2000)
The tubular epithelium of the Drosophila tracheal system forms a network with a stereotyped pattern consisting of cells and branches with distinct identity. The tracheal primordium undergoes primary branching induced by the FGF homolog Branchless, differentiates cells with specialized functions such as fusion cells, which perform target recognition and adhesion during branch fusion, and extends branches toward specific targets. Specification of a unique identity for each primary branch is essential for directed migration, as a defect in either the EGFR or the Dpp pathway leads to a loss of branch identity and the misguidance of tracheal cell migration. Here, we investigate the role of Wingless signaling in the specification of cell and branch identity in the tracheal system. Wingless and its intracellular signal transducer, Armadillo, have multiple functions, including specifying the dorsal trunk through activation of Spalt expression and inducing differentiation of fusion cells in all fusion branches. Moreover, we show that Wingless signaling regulates Notch signaling by stimulating delta expression at the tip of primary branches. These activities of Wingless signaling together specify the shape of the dorsal trunk and other fusion branches.